Aerosol Jet Printing of Hybrid Ti3C2Tx/C Nanospheres for Planar Micro-supercapacitors - Wu, Yu; Lin, Aiping; Zhang, Jidi; Zhao, Danjiao; Fan, Lanlan; Lu, Cheng; Wang, Shufen; Cao, Lei; Gu, Feng (Frontiers in Chemistry, 2022)
When utilized in energy devices, the restacking tendency of MXene Ti3C2Tx inhibits its electrochemical performance. Using aerosol jet printing (AJP) technology, hybrid Ti3C2Tx/C nanospheres are synthesized with C nanoparticle-bonded MXene nanosheets, and the restacking of MXene nanosheets is blocked efficiently. The formation mechanism for hybrid Ti3C2Tx/C nanospheres has been hypothesized, and the Ti3C2Tx/C is anticipated to assemble and shape along the droplet surface in tandem with the Marangoni flow within the droplet. The planar microsupercapacitor devices generated from these hybrid spherical nanostructures with increased interlayer spacing exhibit exceptional areal capacitance performance. This concept offers a straightforward and effective method for constructing 3D-structured MXene with suppressed self-stacking for diverse high-performance micro energy storage devices.